Acquisition of innate B cell properties and generation of autoreactive IgA antibodies by follicular B cells during homeostatic proliferation - Kampe, Laura; Melcher, Christian; Westphal, Katrin; Brand, Korbinian; Föger, Niko; Lee, Kyeong-Hee (Frontiers in Immunology, 2025)
The physiologic process of homeostatic proliferation serves to restore the pool of peripheral lymphocytes in response to lymphopenia. However, functional changes in B cell responses during homeostatic proliferation are still only insufficiently characterized. Mature peripheral B cells consist of functionally distinct B cell subsets, such as adaptive follicular B cells (FoBs) and the innate B cell subsets, marginal zone B cells (MZBs) and B1a B cells. During homeostatic proliferation, B cells undergo antigen-independent clonal expansion and differentiation into antibody-producing plasma cells (PCs). However, it is still largely unknown which B cell lineages are involved in the formation of antibodies in response to lymphopenia and what functional properties these antibodies have. Employing adoptive transfer of different mature B cell subsets into lymphopenic Rag2-/- hosts, we here show that not only innate B cells – MZBs and B1a cells – but also adaptive FoBs were capable to differentiate into PCs and to produce IgM and class-switched IgA serum antibodies in a T cell-independent fashion during homeostatic proliferation. In light of the poor reactivity of FoBs to innate stimulation in vitro, the observed high expansion capacity of FoBs, their sustained repopulation of lymphoid and intestinal organs and their particularly prominent ability to induce class-switched auto-/polyreactive IgA antibodies in this antigen- and T cell-independent system was rather unexpected. These properties, which are more typical for innate B cells, were associated with a striking plasticity of FoBs that transdifferentiate into MZB-like cells under lymphopenic conditions. Together, our study indicates that the reconstitution of antibodies in response to lymphopenia-induced homeostatic B cell proliferation is mainly elicited by innate MZB-like B cell responses via antigen- and T cell-independent pathways resulting in the selection of autoreactive IgA antibodies. In addition, our data point to the pathogenic potential of the conversion of conventional adaptive B cells, which are the most common population of mature B cells, into innate-like B cells and the production of autoreactive IgA antibodies during homeostatic proliferation. This process could also manifest as clinical complication of therapy-induced lymphopenia in the context of transplantation and cancer in human patients.